\(|x-2|+2|x-1|=11\)

c,

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 3 2020

a) \(\left|x-2\right|=3\)

\(\Rightarrow\orbr{\begin{cases}x-2=3\\x-2=-3\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=3+2=5\\x=-3+2=-1\end{cases}}\)

Vậy x=5 hoặc x=-1

3 tháng 3 2020

Ta có :\(\left|x-2\right|=3\)

\(=>\orbr{\begin{cases}x-2=-3\\x-2=3\end{cases}}\)

\(=>\orbr{\begin{cases}x=-1\\x=5\end{cases}}\)

17 tháng 9 2020

a, ( x - 3 ) . ( x - 4 )  = 0              

=> x - 3 = 0 hoặc x - 4 = 0 

Nếu x - 3 = 0 => x = 3 

Nếu x - 4 = 0 => x = 4 

b, (\(\frac{1}{2}\)x  - 4 ) . ( x - \(\frac{1}{4}\)) = 0 

=>(  \(\frac{1}{2}\)x - 4 ) = 0    Hoặc  ( x - \(\frac{1}{4}\)) = 0 

Nếu ( \(\frac{1}{2}\)x - 4 ) = 0  => x = \(\frac{8}{1}\)

Nếu ( x - \(\frac{1}{4}\)) = 0     => x = \(\frac{1}{4}\)

c, (\(\frac{1}{3}\)- x ) . ( \(\frac{1}{2}\)+ 1 : x ) = 0 

=> ( \(\frac{1}{3}\)- x ) = 0 Hoặc ( \(\frac{1}{2}\)+ 1 : x ) = 0

Nếu (\(\frac{1}{3}\)- x ) = 0 => x = \(\frac{1}{3}\)

Nếu ( \(\frac{1}{2}\)+ 1 : x ) = 0 => x = \(\frac{-2}{1}\)

d, ( x + 3 ) . (  x - 4 ) + 2.(x + 3 ) = 0

=> (X + 3 ) = 0 Hoặc  ( x - 4 ) = 0 Hoặc 2. ( x + 3 ) = 0

Nếu x + 3 = 0 => x = 0

Nếu ( x - 4 ) = 0 => x = 4 

Nếu 2.(x + 3) = 0  => x = 3 

# Cụ MAIZ 

17 tháng 9 2020

a. ( x - 3 ) ( x - 4 ) = 0

<=> \(\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\)

<=> \(\orbr{\begin{cases}x=3\\x=4\end{cases}}\)

b. \(\left(\frac{1}{2}x-4\right)\left(x-\frac{1}{4}\right)=0\)

<=> \(\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\)

<=> \(\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)

17 tháng 9 2020

                          Bài làm :

\(a\text{)}...\Leftrightarrow\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=4\end{cases}}\)

\(b\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x=4\\x=0+\frac{1}{4}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)

\(c\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{3}-x=0\\\frac{1}{2}+1\div x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}-0\\1\div x=-\frac{1}{2}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=-2\end{cases}}\)

\(d\text{)}...\Leftrightarrow\left(x+3\right)\left(x-4+2\right)=0\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\Leftrightarrow\orbr{\begin{cases}x+3=0\\x-2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)

Bài làm :

\(a,\left(x-3\right)\left(x-4\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=4\end{cases}}\)

\(b,\left(\frac{1}{2}x-4\right)\left(x-\frac{1}{4}\right)=0\)

\(\Rightarrow\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\Rightarrow\orbr{\begin{cases}\frac{1}{2}x=4\\x=\frac{1}{4}\end{cases}}\Rightarrow\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)

\(c,\left(\frac{1}{3}-x\right).\left(\frac{1}{2}+1:x\right)=0\)

\(\Rightarrow\orbr{\begin{cases}\frac{1}{3}-x=0\\\frac{1}{2}+1:x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=-2\end{cases}}\)

\(d,\left(x+3\right)\left(x-4\right)+2\left(x+3\right)=0\)

\(\Rightarrow\left(x+3\right)\left(x-4+2\right)=0\)

\(\Rightarrow\left(x+3\right)\left(x-2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x+3=0\\x-2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)

Học tốt nhé

17 tháng 9 2020

          Bài làm :

\(a\text{)}...\Leftrightarrow\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=4\end{cases}}\)

\(b\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x=4\\x=0+\frac{1}{4}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)

\(c\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{3}-x=0\\\frac{1}{2}+1\div x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}-0\\1\div x=-\frac{1}{2}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=-2\end{cases}}\)

\(d\text{)}...\Leftrightarrow\left(x+3\right)\left(x-4+2\right)=0\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\Leftrightarrow\orbr{\begin{cases}x+3=0\\x-2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)

7 tháng 8 2020

hihihihi

7 tháng 8 2020

a)  \(\left|\sqrt{2}-x\right|=\sqrt{2}\)

\(\Rightarrow\orbr{\begin{cases}\sqrt{2}-x=\sqrt{2}\\\sqrt{2}-x=-\sqrt{2}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=2\sqrt{2}\end{cases}}}\)

b) \(\left|x+1\right|=\sqrt{3}+2\)

\(\Rightarrow\orbr{\begin{cases}x+1=\sqrt{3}+2\\x+1=-\sqrt{3}-2\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=\sqrt{3}+1\\x=-\sqrt{3}-3\end{cases}}\)

21 tháng 7 2019

a. +) x+2=9              +) x+2=-9 

     => x=7                  =>x=-11

21 tháng 7 2019

a) (x + 2)2 = 81

=> (x + 2)2 = 92

=> \(\orbr{\begin{cases}x+2=-9\\x+2=9\end{cases}}\Rightarrow\orbr{\begin{cases}x=-11\\x=7\end{cases}}\)

b) 5x + 5x + 2 = 650

=> 5x + 5x . 52 = 650

=> 5x + 5x . 25 = 650

=> 5x (25 + 1)   = 650

=> 5x . 26          = 650

=> 5x                 = 650 : 26

=> 5x                 = 25

=> 5x                 = 52

=>   x                 = 2

d) (2x - 1)2 - 5 = 20

=> (2x - 1)2      = 25

=> (2x - 1)2       = 52

=> \(\orbr{\begin{cases}2x-1=5\\2x-1=-5\end{cases}\Rightarrow\orbr{\begin{cases}2x=6\\2x=-4\end{cases}\Rightarrow}\orbr{\begin{cases}x=3\\x=-2\end{cases}}}\) 

g) (x - 1)3 = (x - 1)

=> (x - 1)3 - (x - 1) = 0

=> (x - 1) .[(x - 1)2 - 1] = 0

=> \(\orbr{\begin{cases}x-1=0\\\left(x-1\right)^2-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\\left(x-1\right)^2=1^2\end{cases}\Rightarrow}\orbr{\begin{cases}x=1\\x-1=\pm1\end{cases}}}\)

Nếu x - 1 = 1 

=> x = 2

Nếu x - 1 = -1

=> x = 0

Vậy \(x\in\left\{0;1;2\right\}\)